Configurations of the personal, public, and professional in Facebook users' profiles: content analysis - Hrudka, Orysia (Ukrainian Cultural Studies, 2024)
Background. Social media have become powerful platforms for self-representation and self-presentation. Researchers note that social networks blur the conventional boundaries between personal and public issues and spheres of life. Empirical analysis of personal profiles will help understand what issues (personal, public, or professional) and in what configurations users post on their social networks. The study aims to analyze the posts' meta-themes, types, and general patterns of configurations in 15 personal profiles of the Ukrainian Facebook space. Methods. Content analysis of 50 consecutive posts from 15 profiles of users of different ages, professions, and publicity was applied. Posts have been categorized by meta-themes (personal, professional, public) and types defined in the process of analysis (including dissemination of information about one's project, posts for memorable dates, diary accounting, diary reflection, meme, quote, opinion writing, etc). Results. Differences between the strategies of personal profile usage by public and non-public individuals were found. In particular, non-public users more often focus on personal topics, while public ones focus on professional ones. Popular types of posts were identified, such as diary accounting, diary reflecting, mapping of one's network, and project announcements. It was found that promoting one's own projects, journalism, and essay writing, as well as crowdfunding campaigns, are more common among public figures, while diary reflection, sharing photos, and memes are more prevalent among non-public users. Personal profiles in social networks perform a number of functions, such as being counterparts of live communication and self-presentation, spaces for opinion leadership, and involvement in collective events. Despite the proven diversity of profile management, each user demonstrates integrity and consistency in their approach. Conclusions. Unlike institutions and spaces of modernity, contemporary social networks combine different spheres of life (personal, professional, and public) in one space – in a single personal profile and even a single post. This creates both new opportunities for self-(re)presentation and challenges. Further empirical research involving qualitative methods is relevant for a deeper understanding motivation of users and their perception of the profiles.
Keywords: social media; Facebook; cultural issues; self-representation; socio-cultural transformations; individualism; cultural practices; identity